P185 Development of a bronchiolitis assessment tool in two busy UK district general hospitals: 'bronchiolitis-made-easy'. (June 2019) - Maduemem, Kene; Vasudeva, Dilip; Broodbank, David; Chingale, Amol
Abstract : Background/Aim: Bronchiolitis is one of the commonest causes of hospital presentations during the winter period. It poses a great deal of strain on the health care staff and resources. A targeted assessment tool is thought to provide a prompt and optimal assessment to limit unwarranted investigations and hospital admissions. The acute assessment of children with a clinical diagnosis of bronchiolitis was initially audited with subsequent re-audit using the assessment pro forma. Methods: Children admitted with bronchiolitis between November 2017 and January 2018 in one hospital site were randomly selected. Medical notes were reviewed to evaluate the clinical assessments and treatment(s) offered in comparison with NICE guidance. A pilot study was subsequently performed to assess the use of the new assessment pro forma by medical students and junior doctors. Results: Thirty medical notes were randomly selected for the audit. History of apnoea was inquired in 7 of 20 infants aged 3 months and below. Oral intake was clearly documented in only 36.7% (11/30). Neonatal events were clearly documented in 96.7% (29/30). Documentation of exposure to passive smoking occurred in 23.3% (7/30). Only 50% had documented assessment of hydration status and femoral pulses. Blood tests were requested in 13 infants with clinical indications documented in 7. Sixty-five percent (11/17) had no documented clinical indication for chest radiograph. Inappropriate treatments (bronchodilators, steroids, antibiotics) were initiated in 30% of infants. The pilot study involved 15 volunteers (medical students and junior doctors) on the use of the assessment pro forma in the 2 hospital sites. Analyses of the pro forma demonstrated 100% compliance in all parameters re-audited. Conclusion: The new pro forma has demonstrated its usefulness in targeted assessment of children with suspected bronchiolitis. Well-focused history and examination will safely stratify children to be managed in the community or hospital. The feedbacks received from its use were excellent.